AWARENESS AND ATTITUDES TOWARDS EMERGENCY CONTRACEPTIVES (EC) AMONG UNDERGRADUATE STUDENTS IN MAKURDI NORTH CENTRAL NIGERIA. - MT, Maanongun; AA, Ornguze; PO, Eka; AO, Ojabo; TZ, Swende; SK, Hembah-Hilekaan (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective: The study sought to establish the awareness, utilization and attitude towards the useof EC among female undergraduates.Method: This is a descriptive cross-sectional study that was conducted among 397 femaleundergraduates of the Benue State University, Makurdi between May and June 2016.Results: Out of the 400 subjects recruited 397(99.3%) were analyzed. Most of them 358(90.2%)were 25 years and below. Majority of them 370(93.2%) were single and 186 (49.6%) weresexually active. Of the sexually active, 51(27.4%) had multiple sexual partners and 63(33.9%)had been pregnant at one time or the other. Overall 172(43.3%) were aware of EC and of these,103(59.9%) had utilized them. Awareness was highest among those with multiple sexual partners(74.5%) and those who had had a previous pregnancy (68.3%). The most common type of ECused among the respondents was the Levonorgestrel only (postinor 2) pill 88(85.4%). The mostcommon sources of initial information for those who were aware and those who had used ECrespectively were peers/friends (37.2% and 44.7%)..Conclusion: Awareness and utilization of EC was low among the undergraduate students. Werecommend that efforts should be made to make information about EC and its use available onuniversity campuses.